Victims of Human Trafficking in Thailand: A Study of How Victim’s Right is Protected in Criminal Proceedings - Muangtham, Wanwipa (Asian Interdisciplinary and Sustainability Review, 2019)
No country can evade the threat of transnational organized crime. To cope with transnational crime in form of human trafficking, the United Nations Convention against Transnational Organized Crime along with the Protocol to Prevent, Suppress and Punish Trafficking in Persons, especially Women and Children supplements sets out the legislative measures for states parties to harmonize the provisions for protecting victim and witnesses of trafficking particularly for children and women in their domestic law as these victims and witnesses play an essential role on bringing the trafficker to justice but they are often confronted with the threat of intimidation and retaliation. In the view of fact, the key problems in Thailand which are corruption and miscarriage of justice give a chance for some law enforcements and government officials to be involved in an abuse of power which results in victims and witnesses feeling reluctant to cooperate with the authorities. Therefore, truly comprehensive anti-human trafficking responses which are legislative measures, preventive measures, national coordination and cooperation and international cooperation and coordination must be implemented in Thailand. Equally important is, for some cases which government officials tend to relate to obstruction of justice or corruption, only the relocation of victims and witnesses within Thailand cannot guarantee their safety. The suggestion is the relocation of victims and witnesses to another country which could ensure the safety of victims and witnesses.